PERANAN DEWAN KEAMANAN PERSERIKATAN BANGSA-BANGSA DALAM KRISIS NUKLIR KOREA UTARA - Hanafi Dwi Atmojo; Margareta Siska Widianingrum; Dhani Kristanto Utomo (Faculty of Law Universitas Sebelas Maret, 2015)
This study aims to identify and describe the action done by UN Security Council related to its role in dealing with the nuclear crisis in North Korea as well as assessing the suitability of the UN Security Council action in dealing with the nuclear crisis in North Korea with the provisions of Chapter V-VII of the UN Charter. The type of this research is legal research. The type of data used is secondary data, which consist primary, legal materials, legal materials and secondary and tertiary legal materials. The technique of collects is data library research techniques. The UN Security Councils action in addressing the North Korean nuclear crisis are investigation, recomendation and supporting the Six-Party Talks, it has provided sanctions against North Korea with Resolution 1698, 1718, and 1874. UNSC action is appropriate because it is based on Article 24 paragraph (1) Chapter V, Article 33 paragraph (1) and (2) Chapter VI, Article 34, Chapter VI, Article 39 of Chapter VII 41 Chapter VII of the UN Charter.